Hypercoagulability and thrombotic events in severe SARS-CoV-2 infections (Research, Society and Development, 2023)
COVID-19 pathology caused by SARS-CoV-2 virus infection manifests mainly with respiratory tract symptoms. However, several studies demonstrate characteristics of a systemic disease with repercussions on the cardiovascular, respiratory, gastrointestinal, neurological, hematopoietic and immunological systems. In the homeostasis process, coagulation represents a defense mechanism of the body, however in some individuals there is an exacerbation of this process, giving rise to complications correlated with hypercoagulability and thromboembolic events. This is an integrative review of the literature through data extraction, analysis, synthesis of results and conclusion of articles already published between the years 2020 and 2023. The following databases were used: Lilacs, PubMed, IBECS and MedLine by through the virtual health library. The objective of the work is to carry out an analysis through reviews of scientific articles on the relationship between the hypercoagulable state in patients with severe SARS-CoV-2, given that there is a relatively high incidence of thrombotic and thromboembolic events as a complication of the disease. It is understood that infection with the virus that causes COVID-19 can lead to a state of hypercoagulability, in which there is an increase in serum levels of fibrinogen, D-dimer and some coagulation factors, favoring thromboembolic events, which highlights the need research, prevention and treatment of these, as they present high morbidity and mortality.